Sequência didática e o interacionismo sociodiscursivo na geografia escolar: propostas teórico-metdologógicas - Silva, Wellington Domingos Pereira da [UNESP] (2015)
This work has as main objective to discuss the contribution that the instructional sequence and production of written text genres have on the Geography teaching and learning process of students from the ninth grades of elementary school. For this, we rely on the principles of sociodiscursiveinteracionism by Jean Paul Bronckart, as well as the conceptions of Teaching Sequence and genres by Joaquim Dolz and Bernard Schneuwly, the perspective of discussions on discursive genres by Mikhail Bakhtin. Therefore, we constructed a didactic sequence on the subject Globalization and consumerism and apply this standard in the first quarter of 2014. In the analysis, we seek to observe the results in the teaching learning process, once the activities during the Didactic Sequence allow to see the advances in the fields of language and content. These results show that each student, one way or another, in their written textual productions managed to trace a dialogue with intertexts presented during our intervention. We also note that, prior to implementing the modules of the Sequence, when there was the initial production, the discussion of the students were quite superficial or equivocal about the phenomena depicted. However, in advancing the modules, we realized the incorporation of stronger arguments in the speeches of these students. Another relevant aspect is the creative potential, which despite some difficulties with gender, or with the subject, brought to their textual productions discussions with extremely sharp criticism associated to comical. We noted, finally, that advances with the activities in the light of sequence and genres, were very significant. For the students, there was a greater changeability in their learning (both specific content of Geography, as the mechanisms of language); for the teacher, a new way of thinking and intervene in the teaching learning process within the classroom, breaking with traditional and inefficient due ...